Studies on the Palaeolithic of Western Eurasia : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France).. Volume 14,, Session XVII-4, Session XVII-6 - International Union of Prehistoric and Protohistoric Sciences (2021)
Papers from Session 4 disseminate a wealth of archaeological data from Bavaria to the Russian Plain, and discuss Aurignacian, Gravettian, Epigravettian, and Magdalenian perspectives on lithic tool kits and animal remains. Session 6 was concerned with lithic raw material procurement in the Caucasus and in three areas of the Iberian peninsula.